Selection of Efficient Inhibitors for Caspas-9 according to Structure-Based Pharmacophore Screening Strategy and Molecular Dynamics Simulations - Ansari, Samira; Kamali, Ali Naghi; Bagherzadeh, Kowsar; Amanlou, Masoud; Aghabalazadeh, Sajjad (Trends in Peptide and Protein Sciences, 2020)
Caspases are enzymes which are the main pathways for apoptosis. Any irregulation in their functions causes increase or decrease in cell death, which result in autoimmune disease or cancer, respectively. In this study, structure-based pharmacophore drug discovery method as a virtual screening was used to discover selective inhibitors for caspase-9. This enzyme is an initiator caspase that is the main pathway in Alzheimer’s disease. A pharmacophore model was developed by investigating essential interactions among the reported potent inhibitors employing a docking analysis methodology. Applying pharmacophore virtual screening, nine compounds from both National Cancer Institute (NCI), and ZINC databases were filtered as potent inhibitors of caspase-9. The efficiency of the discovered compounds was further investigated by docking studies. HIGHLIGHTS •Caspase-9 is an important enzyme for apoptosis and its activity is pivotal in cell death. •A computational design of small molecular inhibitors for caspase-9 performed by structure-based pharmacophore model. •9 compounds from both National Cancer Institute (NCI) and ZINC databases were discovered as potent inhibitors.